Distinguishing between factual information and insulting or abusive messages bearing words or phrases in news articles - Mahmud, Altaf; Ahmed, Kazi Zubair (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.